Conjugated bile acids are elevated in severe calcific aortic valve stenosis - Hannah Zhang; Negar Atefi; Arun Surendran; Jun Han; David R. Goodlett; Davinder S. Jassal; Ashish Shah; Amir Ravandi (Journal of Lipid Research, 2025)
Calcific aortic valve (AV) stenosis (CAVS) is a disease associated with significant morbidity and mortality in the aging population. Recently, bile acids have been shown to play a significant role in many disease processes, and untargeted metabolomic analyses of CAVS patient valves have shown a disrupted bile acid pathway. We aimed to understand the changes in human valvular bile acids in relation to CAVS severity. A total of 100 human AVs were collected from patients undergoing AV replacement surgery. Bile acids were quantified by ultrahigh performance liquid chromatography coupled to MS/MS. Patients with mild aortic stenosis (AS) showed a distinct valvular bile acid composition compared with moderate and severe AS groups, with five bile acids being significantly elevated in patients with moderate and severe AS. These included norcholic, nordeoxycholic, glycodeoxycholic, glycocholic, and taurodeoxycholic acid. When classified by calcification score, five species were significantly different between mild and severe AS groups; four bile acids were similar when stratified based on AS severity. Using K-means clustering, we were able to distinguish valve severity by their bile acid composition. Grouping bile acids by conjugation and by primary versus secondary revealed that conjugated primary and secondary bile acids were significantly increased in stenotic valves compared with the mild AS group. Conjugated bile acids are significantly elevated in the valvular tissue of patients with severe calcific AS. These findings suggest a potential link between liver and gut microbiome physiology and bile acid pathways in contributing to the pathophysiology of valvular stenosis.